Clinical Manifestations, Laboratory Findings, and Therapeutic Regimen in Hospitalized Children with Brucellosis in an Iranian Referral Children Medical Centre - Fanni, Fatemeh; Shahbaznejad, Leila; Pourakbari, Babak; Mahmoudi, Shima; Mamishi, Setareh (Journal of Health, Population and Nutrition, 2013)
Brucellosis is considered a known widespread zoonotic disease and is endemic in Mediterranean region, like Iran. This study reviewed the clinical manifestations, laboratory findings, and therapeutic regimen in childhood brucellosis in Iran. In this retrospective study, we reviewed hospital-records of 34 consecutive children with a confirmed diagnosis of brucellosis among a total number of 10,864 patients admitted to Childrens Medical Center, Tehran, Iran, between 2002 and 2010. Among the patients diagnosed with brucellosis, 22 (65%) were admitted during spring and summer. Clinical findings of these patients at admission were arthritis, splenomegaly, hepatomegaly, lymphadenopathy, maculopapular skin rashes, and fever. Anaemia (53%) and leukopenia (33%) were the most common findings in the children. Only one patient had presented with leukocytosis. Four children (12%) were thrombocytopenic, and none of patients had pancytopenia. Blood cultures were positive in 5 patients (23%). Only one patient underwent bone-marrow aspiration and had positive culture for Brucella spp. Positive titres were found in 33 cases (97%) in Wright test, 23 cases (96%) in Coombs test, and 16 patients (72.7%) in 2ME (2-Mercaptoethanol) test. In one case, Wright and Coombs test titres were below 1:80 while Brucella spp. were isolated from blood at the same time. It is concluded, prolonged fever with joint involvement and organomegaly may increase possibility of infection with Brucella spp. Appropriate treatment regimen by more tolerable oral drugs, with a duration of at least 8 weeks, is recommended. J HEALTH POPUL NUTR 2013 Jun; 31(2): 218-222 DOI: http://dx.doi.org/10.3329/jhpn.v31i2.16386